Delayed genital necrosis after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy with Mitomycin-C. Issue 9 (September 2021) - Baron, Ekaterina; Velez-Mejia, Carolina; Sittig, Michelle; Spiliotis, John; Nikiforchin, Andrei; Lopez-Ramirez, Felipe; Gushchin, Vadim; Sardi, Armando
Abstract: Introduction: Genital necrosis (GN) is a rare complication of cytoreductive surgery with hyperthermic intraoperative chemotherapy (CRS/HIPEC) which can be confused with necrotizing fasciitis. We present an analysis of GN after CRS/HIPEC to define its natural history. Methods: We identified patients with GN after CRS/HIPEC at two peritoneal surface malignancy institutions. Patient demographic, surgical, and postoperative data were extracted from prospective databases. Results: Of 1597 CRS/HIPECs performed, 13 patients (0.8%) had GN. The median age was 57 years (IQR: 49–64) and 77% (n = 10) were male. Mitomycin-C was the perfusion agent in all cases of GN (100%). The median time to GN onset after CRS/HIPEC was 64 days (IQR: 60–108) and 2 (15%) patients were receiving systemic chemotherapy at the time of GN onset. Symptoms included severe pain (100%), edema (100%), labial or scrotal skin ulceration (92%), signs of infection (39%), and fever (15%). Seven (54%) patients had thrombocytosis >400 ∗10 9 /L, whereas coagulation tests were within normal reference range in 100% cases. All patients initially underwent conservative treatment, with antibiotic therapy administered in 62% (n = 8). Surgical debridement was performed in 9 (70%) cases with median time after GN onset of 57 (IQR: 8–180). Conclusion: GN is a debilitating complication after CRS/HIPEC with delayed onset and a protracted clinical course. Optimal treatment results could be achieved with initial conservative management until complete lesion demarcation followed by surgical debridement. The pathophysiology of GN is unclear, and we call for other researchers attention to better understand the complication and prevention. Highlights: Genital necrosis is a rare and debilitating complication after CRS/HIPEC It has delayed onset and protracted clinical course with presentation usually >2 months after surgery Due to late presentation, genital necrosis is commonly misdiagnosed as necrotizing fasciitis and Fournier gangrene It should be initially treated conservatively until complete lesion demarcation followed by surgical debridement.